Perceived over Qualification and Cyber Loafing: Mediating Role of Moral Disengagement and Moderating Role of Moral Identity - Aziz, Sundas; Tariq, Amina; Ashraf, Nyela (Annals of Human and Social Sciences, 2024)
This research aims to study the impact of perceived over qualification on cyber loafing with the mediating role of moral disengagement and moderating role of moral identity. Organizations face challenges in hiring and managing employees who perceive themselves as overqualified, which can lead to moral disengagement and cyber loafing. Understanding the impact of perceived over qualification is crucial for talent retention. Data were collected online from 343 employees of Pakistani government and private sector organizations by using convenience sampling technique. Data was processed in SPSS 21. The findings of this research work indicates a positive and significant relationship between perceived over qualification and cyber loafing. Moreover, moral disengagement mediates the relationship between perceived over qualification and cyber loafing. Furthermore, High moral identity moderates the relationship between moral disengagement and cyber loafing. Future research should expand the model, consider additional moderators and mediators such as ethical leadership and ethical climate.